Processos formativos e reflexivos na educação infantil: o aprimoramento da proposta pedagógica do espaço imaculada - Moreira, Giselle Grandi Pires (Universidade do Vale do Rio dos Sinos, 2024)
This study focuses on understanding the role of school management in the context of Early Childhood Education at Colégio dos Jesuítas, located in the city of Juiz de Fora, Minas Gerais, in terms of supporting and promoting teaching practices. In addition, the aim is to see how school management can support and promote them, involving teachers and responsible family members and thus contributing to the improvement of Espaço Imaculada's pedagogical proposal. The theoretical framework addresses collaborative school management, supported by the perspectives of Paro (2014) and Libâneo (2015). It discusses teacher education, highlighting the importance of continuing professional development, based on the ideas of Libâneo (2001) and Nóvoa (2022). Finally, the text examines the curriculum in Early Childhood Education, reflecting on a new conception of education and curriculum that considers pedagogical practices and unwalling childhood, grounded in the works of Fochi (2023) and Barros (2018). For data collection, questionnaires were made available for online completion for ten teachers, five managers and 46 family members responsible for children enrolled in Early Childhood Education. The place where the research was carried out was the Colégio dos Jesuítas, which is part of the Jesuit Education Network and, in turn, is an apostolic instrument of the Society of Jesus. The results point to the importance of ongoing education processes, management support and partnerships with families for pedagogical practice in Early Childhood Education. The participants emphasized the transformations in pedagogical practices within the school environment, stressing that this evolution must accompany the changes observed in the empirical field analyzed. The commitment of the teaching staff was therefore evident to building teaching practices and the importance of collaborative school management in transforming an innovative culture in early childhood education. In view of the above, an intervention proposal was drawn up, which resulted in a continuing education roadmap for teachers in this segment.
Keywords: Educação Infantil; gestão escolar; Formação de professores; Práticas pedagógicas; Early childhood education; School management; Teacher training; Pedagogical practices; ACCNPQ::Ciências Humanas::Educação